2014
DOI: 10.1890/12-2151.1
|View full text |Cite
|
Sign up to set email alerts
|

Spatial occupancy models applied to atlas data show Southern Ground Hornbills strongly depend on protected areas

Abstract: Abstract. Determining the range of a species and exploring species-habitat associations are central questions in ecology and can be answered by analyzing presence-absence data. Often, both the sampling of sites and the desired area of inference involve neighboring sites; thus, positive spatial autocorrelation between these sites is expected. Using survey data for the Southern Ground Hornbill (Bucorvus leadbeateri ) from the Southern African Bird Atlas Project, we compared advantages and disadvantages of three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 29 publications
1
45
0
Order By: Relevance
“…Our approach differs in that we consider the effects of all extant patches in the patch network according to an estimated dispersal kernel in continuous space (see also Risk et al 2011), which allows connectivity to be estimated and predicted across the entire landscape. The major difference here is that, unlike the more phenomenological conditional autoregressive (CAR) or autologistic models that represent implicit processes (Bled et al 2011, Broms et al 2014, we are able to model metapopulation (or patch occupancy) dynamics using an explicit process model, a model of dispersal, which could be further generalized for example through introduction of stage-, age-, or group-specific dispersal coefficients. Dispersal is arguably the most fundamental process driving spatial dynamics in fragmented populations (Hanski and Gaggiotti 2004); our model allows population stage structure and abundance to be considered explicitly when estimating dispersal rates and distances and provides an important tool for investigating the causes and consequence of dispersal (Clobert et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Our approach differs in that we consider the effects of all extant patches in the patch network according to an estimated dispersal kernel in continuous space (see also Risk et al 2011), which allows connectivity to be estimated and predicted across the entire landscape. The major difference here is that, unlike the more phenomenological conditional autoregressive (CAR) or autologistic models that represent implicit processes (Bled et al 2011, Broms et al 2014, we are able to model metapopulation (or patch occupancy) dynamics using an explicit process model, a model of dispersal, which could be further generalized for example through introduction of stage-, age-, or group-specific dispersal coefficients. Dispersal is arguably the most fundamental process driving spatial dynamics in fragmented populations (Hanski and Gaggiotti 2004); our model allows population stage structure and abundance to be considered explicitly when estimating dispersal rates and distances and provides an important tool for investigating the causes and consequence of dispersal (Clobert et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Any taxa with sufficient, reliable, detectability and sampling density are viable candidates for LLA, for example, amphibians (especially frogs), Lepidoptera and Odonata. More complex analytical techniques, such as occupancy modelling, can also be applied where sufficient list data occurs (e.g., Broms et al, 2013).…”
Section: Advantages Of Lla For Impact Evaluationmentioning
confidence: 99%
“…We used the hierarchical spatial occupancy model approach of Johnson et al () because it is effective over large spatial extents, employs a probit mixture framework that resolves issues with multicollinearity and spatial confounding, and improves algorithm convergence. We followed the model‐fitting process described in Broms et al () and first identified supported likelihood‐based occupancy models and then used a hierarchical Bayesian approach to fit the supported models with and without spatial autocorrelation.…”
Section: Methodsmentioning
confidence: 99%
“…We ran each model with 1 chain for 60,000 iterations, discarding the first 10,000 as burn‐in, and employed a thinning rate of 1/5, for a total sample of 10,000 iterations per model (after Broms et al ). The Moran cut used in the spatial model was 10% of the number of sites, and the priors for the spatial component of the model were τ ∟ Îł (0.5, 0.0005; after Broms et al ). We estimated median βs and 95% credible intervals from the stocc models.…”
Section: Methodsmentioning
confidence: 99%